2006
DOI: 10.1177/154193120605001616
|View full text |Cite
|
Sign up to set email alerts
|

Active Regulation of Speed during a Simulated Low-Altitude Flight Task

Abstract: This study examined active regulation of speed during a low-altitude flight task as a function of global optical flow rate, speed, and the presence or absence of a concurrent altitude disturbance. The results showed that altitude clearly had an impact on speed control. Control of speed was much more difficult when altitude disturbances were present. Even in the no altitude disturbance conditions, performance tended to be best at lower altitudes. Consistent with previous research, the results suggest that speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…Hence, if GOFR is used to perceive and control forward speed, cross-talk between altitude changes and speed control will result. Using a speed maintenance task originally developed by Bennett, Flach, McEwen & Russell (2006), Wotring et al (2008) observed exactly this type of speed-altitude cross-talk in simulations of low-altitude flight over a planar surface. This cross-talk is particularly dangerous for general aviation flight at low altitude because of the tradeoff between air speed and altitude dictated by gravity and aerodynamics.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Hence, if GOFR is used to perceive and control forward speed, cross-talk between altitude changes and speed control will result. Using a speed maintenance task originally developed by Bennett, Flach, McEwen & Russell (2006), Wotring et al (2008) observed exactly this type of speed-altitude cross-talk in simulations of low-altitude flight over a planar surface. This cross-talk is particularly dangerous for general aviation flight at low altitude because of the tradeoff between air speed and altitude dictated by gravity and aerodynamics.…”
Section: Introductionmentioning
confidence: 81%
“…The joystick gains and disturbance time series were subjected to spectral analysis in a manner similar to Bennett et al (2006) and Wotring et al (2008).…”
Section: Spectral Analysis Of Joystick Amplitude At Altitude and Speementioning
confidence: 99%
“…The joystick gains and disturbance time series were subjected to spectral analysis in a manner similar to Bennett et al (2006), Wotring et al (2008), and Adamic et al (2010).…”
Section: Discussionmentioning
confidence: 99%
“…While previous research showed that changes in GOFR due to altitude changes can affect judgments of speed (Ballard, Roach, & Dyre, 1998;Larish & Flach, 1990;Owen & Wolpert, 1984), to date there is no conclusive evidence that altitude changes induce inappropriate control of speed. Bennett, Flach, McEwen, and Russell (2006) developed a sophisticated methodology to examine this issue. Participants in their study attempted to maintain constant forward speed during a simulation of low-altitude flight over a textured planar surface with a clear textureless sky.…”
Section: Introductionmentioning
confidence: 99%
“…Two methodological features of the Bennett et al (2006) study might explain why they failed to find reliable cross-talk between altitude changes and speed control. First, Bennett et al used a ground texture that consisted of a low spatial frequency checkerboard pattern (See Figure 1a).…”
Section: Introductionmentioning
confidence: 99%